The Effect of Sustainability Reporting Disclosure on Profitability with Good Corporate Governance as a Moderating Variable - Rustandi, Dede (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to examine the effect of Sustainability Reporting Disclosure (SRD) on corporate profitability, with Good Corporate Governance (GCG) as a moderating variable. The research focuses on mining companies listed on the Indonesia Stock Exchange (IDX). Profitability is measured using Return on Assets (ROA), while SRD is assessed through a sustainability disclosure index based on the Global Reporting Initiative (GRI) guidelines. GCG is proxied by corporate governance mechanisms, including the proportion of independent commissioners and the existence of an audit committee. This research applies a quantitative approach using panel data regression and Moderated Regression Analysis (MRA). Secondary data were collected from companies’ annual reports and financial statements during the observation period. The results indicate that Sustainability Reporting Disclosure has a positive effect on corporate profitability. Furthermore, Good Corporate Governance also positively influences profitability. The moderating analysis reveals that GCG strengthens the relationship between SRD and ROA. These findings suggest that sustainability disclosure supported by strong corporate governance enhances stakeholder trust, improves transparency, and encourages more efficient asset utilization, ultimately leading to better financial performance. This study contributes to the sustainability and corporate governance literature by providing empirical evidence from the Indonesian mining sector.